2005
DOI: 10.1016/j.jorganchem.2005.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion of molybdenocene dichloride (Cp2MoCl2) in 2-hydroxypropyl- and trimethyl-β-cyclodextrin: Structural and biological properties

Abstract: Organometallic-cyclodextrin inclusion compounds were obtained by the treatment of molybdenocene dichloride (Cp 2 MoCl 2 ) with the modified cyclodextrins (CDs) heptakis-2,3,6-tri-O-methyl-b-CD (TRIMEB) and 2-hydroxypropyl-b-CD (HPbCD) in aqueous solution. The products were isolated by liophilisation and characterised in the solid-state by powder XRD, thermogravimetric analysis, Raman and FTIR spectroscopy, and 13 C CP MAS NMR spectroscopy. The results are consistent with inclusion of Cp 2 MoCl 2 , rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 39 publications
6
52
0
Order By: Relevance
“…Although such a feature is somewhat uncommon for TRIMEB Fig. 3 Laboratory X-ray diffraction patterns and packing mode schematics for b-CD (bottom), the guest 2 (middle) and compound 4 (top) compounds with metal guests, a similar behavior was observed in some of our previous work with TRIMEB adducts of metallocenes (M = Mo, Nb) (Pereira et al 2007;Braga et al 2005Braga et al , 2001. This same behavior was observed in the TRIMEBÁ[Ru( [9] aneS 3 )bpyCl]Cl adduct , thus suggesting that it may be a characteristic of TRIMEB-encapsulated Ru(II) trithyacyclononane polypyridyl complexes.…”
Section: X-ray Diffraction Studiessupporting
confidence: 68%
See 1 more Smart Citation
“…Although such a feature is somewhat uncommon for TRIMEB Fig. 3 Laboratory X-ray diffraction patterns and packing mode schematics for b-CD (bottom), the guest 2 (middle) and compound 4 (top) compounds with metal guests, a similar behavior was observed in some of our previous work with TRIMEB adducts of metallocenes (M = Mo, Nb) (Pereira et al 2007;Braga et al 2005Braga et al , 2001. This same behavior was observed in the TRIMEBÁ[Ru( [9] aneS 3 )bpyCl]Cl adduct , thus suggesting that it may be a characteristic of TRIMEB-encapsulated Ru(II) trithyacyclononane polypyridyl complexes.…”
Section: X-ray Diffraction Studiessupporting
confidence: 68%
“…Recent work on CD inclusion of the compounds Cp 2 MCl 2 (Cp = cyclopentadienyl, M = Nb, Mo) (Pereira et al 2007;Braga et al 2005Braga et al , 2001 showed an enhanced antitumoral action, in particular for TRIMEBÁCp 2 MoCl 2 (Braga et al 2005). b-CD was also shown to enhance the cytotoxic activity of trans Pt(dipyridine)Cl 2 by improvement of its aqueous solubility (Horvath et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Suitable guests include transition-metal complexes and organometallic compounds bearing hydrophobic ligands such as cyclopentadienyl (Cp = g 5 -C 5 H 5 ) and g 6 -arene groups [4][5][6], capable of docking into the host cavity by non-covalent bonding (either van der Waals or charge-transfer interactions). We have explored the protecting and bio-delivery properties of these hosts to enhance the activity of antitumour metal compounds such as ferrocene derivatives [7] and metallocene dihalides, in particular Cp 2 MCl 2 (Cp = cyclopentadienyl, M = Nb, Mo) [8][9][10]. In particular, cytotoxic assays carried out for pure and included molybdenocene dichloride showed a higher activity upon encapsulation, in particular when using permethylated b-cyclodextrin (TRIMEB) [9].…”
Section: Introductionmentioning
confidence: 99%
“…We have explored the protecting and bio-delivery properties of these hosts to enhance the activity of antitumour metal compounds such as ferrocene derivatives [7] and metallocene dihalides, in particular Cp 2 MCl 2 (Cp = cyclopentadienyl, M = Nb, Mo) [8][9][10]. In particular, cytotoxic assays carried out for pure and included molybdenocene dichloride showed a higher activity upon encapsulation, in particular when using permethylated b-cyclodextrin (TRIMEB) [9]. We have also used cyclodextrin encapsulation to modulate the activity of carbonyl organometallics such as CpFe(CO) 2 X (X = Cl, CN) [11][12][13], Cp 0 Mo(g 3 -C 3 H 5 )(CO) 2 [14], CpMo(LL)(CO) 2 (L = 2 Â CH 3 CN or LL = 2,2 0 -bis-imidazole) [15] and CpMo(CO) 3 CH 2 CONH 2 [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation